Faste penge og flydende kød: Materialitet og neoklassisk økonomi i Zolas Nana og Penge - Gammelgaard, Signe Leth (K&K - Kultur og Klasse, 2017)
This article examines the dynamics of matter and signifiers in Zola’s two novels Nana (1880) and Money (1891). Though Zola’s novels are often read with a focus on capital and economics workings, the context of marginalist economics contemporaneous to Zola is only vaguely described. In drawing upon Jean-Joseph Goux’s work on marginalism and Zola, this topic is addressed, and the article discusses desire, fluidity, scarcity, and value and relates this to the depiction of a disintegrating matter in Nana, and to the motifs of flesh and gold running through the novel. In the reading of Money, the focus is on reckless desire and imagination gone awry, and the push towards an increasingly disconnected abstraction that allows for rapid circulation of values. Here, the two main speculative duelists are seen as representatives of two economic paradigms, and the article finally discusses the depiction of materiality and the uses of this in the novels in the context of a society where values, in the words of Goux, are increasingly fluid and mobile.